The reliability of an adolescent dietary pattern identified using reduced-rank regression: comparison of a FFQ and 3 d food record. - Appannah, G; Pot, G; O'Sullivan, T; Oddy, W; Jebb, SA; Ambrosini, G (2014)
Despite the increasing use of dietary patterns (DP) to study diet and health outcomes, relatively few studies have examined the reliability of DP using different dietary assessment methods. Reduced-rank regression (RRR) is an emerging statistical method that incorporates a priori information to characterise DP related to specific outcomes of interest. The aim of the present study was to compare DP identified using the RRR method in a FFQ with those in a 3 d food record (FR). Participants were 783 adolescents from the Western Australian Pregnancy (Raine) Cohort Study who completed both a FFQ and FR at 14 years of age. A similar 'energy-dense, high-fat and low-fibre' DP was identified in the FFQ and FR that was characterised by high intakes of processed meat and sugar-sweetened beverages, and low intakes of vegetables and fresh fruit. Nutrient profiles for this DP were consistent in the FFQ and FR. Pearson's correlation coefficient between participants' z-scores for the DP identified in the FFQ and FR was 0·35 for girls and 0·49 for boys (P< 0·05). The mean difference between DP z-scores derived from the FFQ and FR was -0·08 (95 % CI -0·21, 0·04) for girls and -0·05 (95 % CI -0·17, 0·07) for boys. The 95 % limits of agreement were -2·55 to 2·39 for girls and -2·52 to 2·41 for boys. These findings suggest that very similar DP may be identified and their z-scores show modest agreement when applying the RRR method to dietary intake data collected from adolescents using a FFQ or FR.